Mechanical Properties of Epoxy Composite Reinforced with Spent Coffee Ground and Coffee Husk - Etanto Heiliano Wijayanto; Al Ichlas Imran; Januar Parlaungan Siregar; Mohd Ruzaimi Mat Rejab; Tezara Cionita; Wisnu Prayogo; Deni Fajar Fitriyana; Rozanna Dewi; Thomas Junaedi; Agustinus Purna Irawan (Advance Sustainable Science Engineering and Technology, 2025)
This study aims to investigate the effect of increasing the concentration of natural filler on the mechanical properties of Spent Coffee Ground (SCG) / Coffee Husk (CH) reinforced epoxy matrix composite. The materials used in this study are epoxy resin as a matrix and waste coffee grounds and coffee husks as natural fillers with sizes of 100-mesh and concentrations of 10, 20, and 30 wt.%. The results showed that SCG 10 wt.% produced the best mechanical properties compared to the other samples based on tensile strength (19.58 MPa), tensile modulus (1.70 GPa), flexural strength (44.55 MPa), and flexural modulus (2.32 GPa). On the other hand, CH 30 wt.% contributed the highest hardness value of 50.33 HRB compared to other samples. The findings in this study prove that the appropriate composition will affect the compatibility between the filler and the matrix, thus impacting the mechanical properties of the composite. This phenomenon can be seen based on microscope analysis, which shows a strong interaction between the matrix and filler and the formation of voids and agglomeration